O espaço formativo da RPS e as necessidades de formação dos professores: atendidas ou não? - Aveledo, Edilene Aparecida Barros da Silva (2018)
The objective of this study was to investigate how the Weekly Pedagogical Meetings (WPM) take place inside a daycare center located in a city adjacent to the city of São Paulo, since teachers complain that these meetings do not meet their training needs. The ethnographic research analyzed in which aspects the WPM meets the training needs of teachers and in which it does not contemplate them, in order to re-signify: the end-goal of WPM as a formative space; the attendance to the training needs of teachers; children's learning; the moments of study, exchange, evaluation and collective decision that guarantee the collaborative teaching-learning process, in a nursery that is part of a municipal education network, with the educational guidelines of its policy. As a hypothesis, it was considered that the Pedagogical Coordinator (PC) has planned WPM with the aim of this space - the continuous formation of the teachers -, but its methodology is restricted to its own reading of the needs of the teachers, without to listen to these professionals, disregarding their history, their culture and the identity of the school. Initially, the picture of the education of the city and its peculiarities is presented, The history of Early Childhood Education and its trajectory in the municipality is also reported. Next, the importance of continuing education and the role of PC to ensure teacher-centered teacher training in the perspective of collaborative networking in the teacher training process is presented. The methodology used in the research involved teachers and PC. The data were collected through a questionnaire, interview, documentary analysis, and records of in situ observations, carried out by the researcher. The theoretical basis of the research is based on the studies of Placco (2003; 2006; 2010; 2012; 2013; 2017), Almeida (2003; 2012; 2016), André (2005; 2010; 2016), Souza (2001; 2012), Tardif (2014), Dubar (2005), Ciampa (1986), among others, about school-centered training and teacher identity. The analysis of the data shows that the greater training need of teachers is related to the practice developed in the classroom, although it reveals the predominance of contradictions, regarding the perception of teachers feel - or not - contemplated in their needs. The contradictory answers also took place regarding the listening and the possibilities of participation of the teachers during the meetings. The analysis also pointed out that the three-hour meetings during the night are tiring and that, at times, there is a loss of focus of the discussions, evidencing the need to elaborate guidelines that are more articulated to the real needs of the teachers. Strong interference was also identified with the demands of the Secretary of Education in the definition of the guidelines, which compromises the time of meetings and meeting the demands of teachers. The need for investment in interpersonal and collective relations was also perceived as a way to reduce the incidence of subjects discussed by teachers in informal spaces, called in the research as "pedagogical corridors". Finally, the need for continued strengthening of the role of the PC is underscored